Specific affect regulation impairments in major depression - Brockmeyer, Timo (2012)
Impairments in affect regulation as well as cognitive reactivity have been considered to play important roles in the development, maintenance, and recurrence of major depressive disorder (MDD). However, there is a lack of studies investigating, (a) whether certain difficulties in emotion regulation are specific for MDD, (b) whether certain meta-mood beliefs are associated with an increased risk for MDD, and (c) whether reduced abilities to engage in mood-incongruent information processing and to disengage from negative information are associated with depression vulnerability, and whether those specific mood regulation processes underlie the mechanism of cognitive reactivity. Therefore, Study 1 of this dissertation compared patients with MDD with a clinical and a healthy control group regarding a comprehensive set of central and clinically relevant emotion regulation difficulties. Study 2 investigated two specific kinds of meta-mood beliefs [i.e., generalized negative mood regulation (NMR) expectancies and a generalized motive to avoid emotional experience (EA)] in formerly-depressed and never-depressed subjects. Finally, Study 3 tested whether two specific mood regulation processes (i.e., mood-incongruent information processing and disengagement from negative information) differentially appear in vulnerable and non-vulnerable individuals, and whether they can account for differences in cognitive reactivity. Patients with MDD reported greater emotion regulation difficulties than healthy controls and did not differ from the clinical control group regarding difficulties with the experience and differentiation of emotions, however, patients with MDD reported greater difficulties than clinical controls regarding the attenuation and modulation of emotions (Study 1). As expected, vulnerable individuals reported lower NMR expectancies and stronger EA as compared to non-vulnerable individuals, and NMR expectancies were furthermore found to be inversely associated with EA (Study 2). In the second but not in the first phase of an autobiographical memory task, vulnerable subjects retrieved fewer mood-incongruent (positively toned) emotion words than non-vulnerable subjects (Study 3). Furthermore, vulnerable subjects with a high cognitive reactivity retrieved more negatively toned emotion words. For non-vulnerable subjects a different pattern occurred: Subjects with a high cognitive reactivity retrieved less positively toned emotion words. The findings of the three studies suggest that emotion regulation difficulties constitute transdiagnostic phenomena, and that MDD may be characterized by particularly broad and pronounced deficits in this domain. The results also suggest that maladaptive meta-mood beliefs are associated with depression vulnerability and that individuals with low confidence in their negative mood regulation abilities are concurrently characterized by a stronger avoidance of emotional experience. Furthermore, the results suggest that a reduced ability of mood-incongruent information processing is associated with depression vulnerability, and that two different memory processes of mood regulation may account for cognitive reactivity in individuals who are at high versus low risk for depression. The cross-sectional designs and the use of self-report measures as well as the relatively small sample sizes in two of the studies limit the interpretation of the obtained results. Notwithstanding, the findings of these three studies call for an implementation of specific elements that foster adaptive affect regulation (e.g., computer-assisted training of cognitive processes) into existing treatment packages for MDD.
Keywords: Hochschulschrift; Regulation; Affekt; Depression